Could light-curing time, post-space region and cyclic fatigue affect the nanomechanical behavior of a dual-curing cement for fiber post luting?. (January 2022) - Serino, Gianpaolo; Comba, Allegra; Baldi, Andrea; Carossa, Massimo; Baldissara, Paolo; Bignardi, Cristina; Audenino, Alberto; Torres, Carlos Gomes Rocha; Scotti, Nicola
Abstract: Objective: To evaluate the effects of curing time, post-space region and cyclic fatigue on the micromechanical properties of a fiber-post luting cement. The null hypotheses were that (1) curing time, (2) fatigue and (3) post-space region does not affect the nanoindentation modulus and hardness of the dual-curing cement. Materials and methods: 48 premolars were endodontically treated and a class I cavity and 8 mm deep post space was prepared. Fiber posts were luted with a universal, dualized adhesive system and a dual-curing cement following manufacturer's instructions. Specimens were divided into three groups (16 specimens for each group) according to light-curing time (no light-curing, 20 s light-curing and 120 s light-curing), which was performed with a LED lamp at 1000 mW/cm 2. The coronal part of the cavity was restored using a nano-filled resin composite. After 24 h, 8 specimens for each group were randomly extract in order to undergo to fatigue test in wet condition through a chewing simulator, while the other specimens were kept in distilled water as benchmark. All the restored teeth were then sectioned in 1 mm thick slices perpendicularly to the fiber post axis. Specimen slices were classified in coronal and apical to be tested through a nanoindenter. Data were analyzed through Kruskal-Wallis test with a significance level of 1%, in order to evaluate the influence of treatments (i.e., curing time and cyclic loading) on the micromechanical properties of the tested luting cement. Results: Both fatigue and curing time significantly influenced nanoindentation modulus and hardness of dual-curing cement (p < 0.01). No significant differences were reported for post space region. A significant interaction was found among the analyzed factors (p < 0.01). Significance: 120 s light-curing time is recommended in order to achieve optimal mechanical proprieties, independently from post space region and cyclic fatigue. As matter of fact, 120 s light-curing allowed to prevent strain hardening induced by the fatigue simulation. Graphical abstract: Image 1 Highlights: An extended lightcuring time of 120 s is suggested to obtain the best mechanical properties from the tested cement. Longer curing time seems to have the ability to confer mechanical stability after cyclic fatigue. Tested dual-curing cement showed a strain-hardening behavior.